Peran Media Globe dalam Meningkatkan Kemampuan Berpikir Kritis Siswa pada Materi IPS di Sekolah Dasar - Santika Buwana (Program Studi Pendidikan Guru Madrasah Ibtidaiyah Institut Agama Islam Negeri Sorong, 2019)
This study aims to analyze the role of globe media in enhancing students' critical thinking skills in Social Studies (IPS) learning at elementary schools. The research employed a literature study approach with descriptive qualitative methods. Data were collected from various relevant literature sources, including accredited journals, books, and proceedings published between 2021-2025, and analyzed using content analysis techniques. The findings reveal three main roles of globe media: (1) as a spatial visualization tool that transforms abstract geographical concepts into concrete representations; (2) as a catalyst for inquiry-based learning that stimulates critical questions and analytical thinking; and (3) as a facilitator for developing multidimensional thinking through direct observation and manipulation. The study demonstrates that globe media effectively improves students' critical thinking abilities, evidenced by significant increases in analyzing, evaluating, and synthesizing geographical information. Students showed enhanced capability in identifying spatial relationships, comparing geographical phenomena, and making evidence-based conclusions. Furthermore, there is a significant positive correlation between globe media utilization and critical thinking improvement, particularly in analytical, evaluative, and creative thinking dimensions. The study concludes that globe media serves as an innovative and effective instructional strategy for optimizing critical thinking development in elementary Social Studies education.